Sirkulasi Virus Flu Burung Subtipe H5 pada Unggas di Jawa Barat, Banten, dan Jawa Timur Sepanjang Tahun 2008-2009 (CIRCULATION OF AVIAN INFLUENZA OF H5 SUBTYPE ON BIRDS IN WEST JAVA, BANTEN AND EAST JAVA DURING 2008-2009) - Hewajuli, Dyah Ayu; Dharmayanti, Ni Luh Putu Indi (Jurnal Veteriner; Vol 13 No 3 (2012), 2013)
The epidemic of avian influenza (AI) in Indonesia initially occurred at the end of 2003 which caused100% death of the affected chickens. It was caused by avian influenza virus (AIV) subtype H5. Recent datashowed that highly pathogenic avian influenza (HPAI)-H5N1 virus is still endemic among bird populationin Indonesia. A study was therefore conducted to find out the distribution of AIV-H5N1 in several regionsin Indonesia. Reverse transcriptase-polymerase chain reaction (RT-PCR) was used to detect the presenceof AI-H5 virus and hemagglutination inhibition (HI) test was used to detect the presence of anti-AIV-H5antibody. Results showed that anti-AIV-H5 antibody was detected in 36 % and was not detected in 64% oftested birds in West Java, Banten and East Java. The AIV-H5 antibody titer varied from low to high titer.The AIV-H5 was detected in samples from Cianjur (30%), Blitar (1.9&), Serang (12.5%) and pandeglang(17.5%). It was evident that AIV-H5 is still endemic in Indonesia.
Keywords: identification, AI of subtype H5, HI and RT-PCR